Comparative analysis of the removal and transformation of 10 typical pharmaceutical and personal care products in secondary treatment of sewage: A case study of two biological treatment processes. Issue 3 (June 2022) - Lin, Han; Huang, Liangzhao; Gao, Zhihan; Lin, Wenting; Ren, Yuan
Abstract: To reduce the occurrence of PPCPs in the environment, its removal in wastewater treatment plants (WWTPs) has attracted much attention. This study reported the removal characteristics of 10 typical PPCPs in two biological treatment processes: blast aeration and UNITANK. The results demonstrated that caffeine (CAF), bezafibrate (BZB), gemfibrozil (GFB), metoprolol (MET), sulfamethoxazole (SMX), and sulfamerazine (SMZ) were mainly removed through biodegradation. Among them, the removal efficiency of CAF was the largest (>85%), and MET was the lowest (<30%). Sulfadiazine (SDZ), naproxen (NPX), sulpiride (SUL), and ofloxacin (OFX) were removed through the combined effect of biodegradation and sludge adsorption. During biotransformation of sulfonamides (SAs), MET, and SUL, some of the conjugates were decomposed into their parent forms again. The results revealed that the adsorption of drugs was correlated with octanol-water partition coefficient (Kow ) and electrostatic interaction. The biodegradation efficiency was affected by oxygen supply conditions. The facultative environment, longer sludge retention time (SRT) and hydraulic retention time (HRT) were positively correlated with the removal of most drugs (CAF, SUL, GFB, MET, NPX, OFX, SDZ, SMX). This paper summarized the similarities and differences of drugs' removal characteristics under different processes and wish to provide useful suggestion for the removal technology of PPCPs in WWTP. Graphical Abstract: ga1 Highlights: NPX, OFX, SUL, SDZ are mainly removed by sludge adsorption. Facultative condition is fit for CAF, NPX, and SMX's removal. SDZ, SMZ and BZB prefer aerobic condition while GFB had no O2 preference. The release of conjugations increased the concentrations of SA, MET, NPX and SUL. The longer HRT is beneficial to the removal of CAF, MET, OFX, SUL, SMX.